PENGARUH PENDAPATAN KELUARGA DAN LITERASI EKONOMI TERHADAP PERILAKU KONSUMTIF MAHASISWA JURUSAN PENDIDIKAN EKONOMI FEB UNIVERSITAS NEGERI GORONTALO ANGKATAN 2021 - Eka Putri Mulyani Kiraman; Roy Hasiru; Imam Prawiranegara Gani; Agil Bahsoan; Abdulrahim Maruwae (Journal of Economic and Business Education, 2025)
This study aims to determine the influence of family income and economic literacy on the consumptive behavior of Economics Education students, Faculty of Economics and Business, Universitas Negeri Gorontalo, Class of 2021. The study employed a quantitative approach. Primary data were obtained through questionnaires distributed to students of the 2021 cohort. The total sample size was 63 respondents. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The regression test results show a determination coefficient (R2) value of R 0,856 and R Square = 0,748. This indicates that the regression model explains that the variables of Family Income (X1) and Economic Literacy (X2) influence the Consumptive Behavior of Economics Education students by 74,8%. Meanwhile, the remaining variation is influenced by other variables not examined in this study.